2005
DOI: 10.1074/jbc.m409399200
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Mitochondrial DNA Causes Impaired Glucose Utilization and Insulin Resistance in L6 GLUT4myc Myocytes

Abstract: Mitochondrial dysfunction contributes to a number of human diseases, such as hyperlipidemia, obesity, and diabetes. The mutation and reduction of mitochondrial DNA (mtDNA) have been suggested as factors in the pathogenesis of diabetes. To elucidate the association of cellular mtDNA content and insulin resistance, we produced L6 GLUT4myc myocytes depleted of mtDNA by long term treatment with ethidium bromide. L6 GLUT4myc cells cultured with 0.2 g/ml ethidium bromide (termed depleted cells) revealed a marked dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 73 publications
(66 reference statements)
2
47
0
Order By: Relevance
“…First, how does O 2 •Ϫ produced in the mitochondria regulate the translocation of GLUT4 to the plasma membrane? Intriguingly, cells that lack mitochondria are not insulin responsive (31), suggesting that the insulin signal must traverse this organelle as a checkpoint before signaling to GLUT4. Second, is mitochondrial antioxidant therapy likely to be of benefit in the treatment of metabolic disease?…”
Section: Discussionmentioning
confidence: 99%
“…First, how does O 2 •Ϫ produced in the mitochondria regulate the translocation of GLUT4 to the plasma membrane? Intriguingly, cells that lack mitochondria are not insulin responsive (31), suggesting that the insulin signal must traverse this organelle as a checkpoint before signaling to GLUT4. Second, is mitochondrial antioxidant therapy likely to be of benefit in the treatment of metabolic disease?…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Park et al [43] showed that reductions in Irs1 expression and insulin-stimulated phosphorylation of IRS1 and Akt2/protein kinase B are associated with insulin resistance in L6 Glut4myc myocytes, where 95% of mtDNA was depleted by EtBr treatment. They showed no discernible changes in total SLC2A4, whereas we observed reduced SLC2A4 production in oligomycin-or EtBr-treated C2C12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The control parental L6 GLUT4myc myocytes were maintained for the same time period in normal culture medium. The mtDNA content of L6 GLUT4myc myocytes cultured with or without EtBr was monitored routinely by amplifying genomic DNA as described previously (2). HEK293 and SK-Hep1 cells were cultured in Dulbecco's modified Eagle's medium with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…After amplification, melting curve analysis and agarose-gel electrophoresis verified the authenticity of the PCR products. The qRT-PCR results were analyzed using Rotor-Gene analysis software version 6.0 (Corbett Research) as described previously (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation